Pengaruh Karakteristik Individu, Karakteristik Kerja dan Karakteristik Organisasi Terhadap Kepuasan Kerja yang Implikasi Terhadap Kinerja Karyawan PT. Metrografi Kendari - Sardiman, Sardiman; Madjid, Rahmat; Ruslan, Ruslan (ECONOMETRICS:Journal of Sustainable Economics and Management, 2025)
This study aims to test and analyze whether individual characteristics, job characteristics, organizational characteristics affect employee performance through job satisfaction at PT. Metro Graphia Kendari. And which of these characteristics has the most dominant influence. To answer the problem, an empirical research model was developed using 5 research variables, individual characteristics, job characteristics, organizational characteristics, job satisfaction and employee performance. Then 10 research hypotheses were formulated. This quantitative research used primary data obtained directly from 30 respondents through the distribution of questionnaires to employees of PT. Metro Graphia Kendari, and uses SEM-PLS analysis techniques in its data processing.  This study confirmed with the results that only individual characteristics, organizational characteristics and job satisfaction had a significant effect on employee performance, different results were shown by job characteristics that did not have a significant effect on employee performance. Meanwhile, job satisfaction that is tested as an intermediary plays a significant mediating role only on the influence of individual characteristics on employee performance